Analisis strategi bisnis menggunakan digital marketing pada UMKM pasca pandemi covid-19 - Muhammad Farhan Rizky; Erwin Permana (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Studies on business strategy analysis using digital marketing are quite a lot done for large company loci. But the study of business strategy analysis using digital marketing for MSMEs is still growing. This study aims to analyze business strategies using digital marketing for MSMEs after the COVID-19 pandemic. The research was conducted with a descriptive qualitative approach. The data was obtained through searching and observing various digital applications related to MSME marketing. The results showed that in the post-covid-19 pandemic, there was a habit of people who like to shop online and a business strategy was needed to deal with this and to maintain the existence of MSMEs. with digital marketing. Business strategies can be implemented in post-pandemic MSMEs as a digitalization strategy using digital marketing, by applying search engine marketing, digital content marketing, Pay-per-click Ads, to influencer marketing. Although the pandemic has begun to end, it is believed that the use of digital media will not decrease